Silicon carbide-polyethylene composite material with laser responsiveness and preparation method thereof
Through wet nanodispersion technology, silicon carbide waste is combined with polyethylene to prepare laser-responsive silicon carbide-polyethylene composite materials, which solves the problems of resource waste and environmental pollution, and achieves the improvement of material performance and efficient utilization of resources.
Patent Information
- Application Number
- CN202510009102.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively utilize silicon carbide waste generated by multi-wire cutting, resulting in waste of resources and environmental pollution.
Through wet nanodispersion technology, silicon carbide waste generated by multi-wire cutting is composited with polyethylene to prepare a laser-responsive silicon carbide-polyethylene composite material.
The resource utilization of silicon carbide waste has been realized, the physical properties and laser response capabilities of the material have been improved, excellent mechanical properties and thermal response behaviors have broad application prospects.
Smart Images

Figure BDA0005227830110000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon carbide, and in particular to a silicon carbide-polyethylene composite material with laser responsiveness and a preparation method thereof. Background Art
[0002] With the rapid development of laser technology, laser-responsive materials have been widely used in the fields of intelligent manufacturing, flexible electronics, information encryption and sensing. Such materials usually undergo physical or chemical changes under the action of lasers, such as local heating, deformation, melting or color change, thereby achieving precise functional response.
[0003] Silicon carbide (SiC), as a functional material with excellent performance, has attracted much attention due to its unique photothermal effect, mechanical strength and thermal stability. If silicon carbide is applied to composite materials, it has the following advantages: Photothermal effect: Silicon carbide can efficiently absorb laser energy, especially lasers in the infrared band, and quickly convert it into thermal energy to achieve high-sensitivity response. Enhanced mechanical properties: Silicon carbide particles have high hardness and high modulus, which can significantly enhance the mechanical properties of composite materials, including tensile strength, hardness and wear resistance. Thermal stability and chemical resistance: The excellent performance of silicon carbide in high temperature and harsh environment makes composite materials suitable for harsh conditions.
[0004] As an important means of processing silicon carbide, multi-wire cutting technology will produce a large amount of fine fragments and powder. These silicon carbide wastes have not been fully utilized for a long time, which not only wastes resources but also may cause environmental pollution. Polyethylene, as a widely used thermoplastic polymer, has the advantages of low cost, easy processing, good flexibility and strong chemical stability.
[0005] If the silicon carbide waste produced by multi-wire cutting is compounded with polyethylene to prepare high-performance laser-responsive materials, it will not only improve the physical properties of the material and give the material laser responsiveness, but also achieve resource utilization. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a silicon carbide-polyethylene composite material with laser responsiveness and a preparation method thereof, the preparation method comprising: preparing a silicon carbide dispersion using silicon carbide waste, dissolving low-density polyethylene particles to prepare a polyethylene solution, adding the silicon carbide dispersion to the polyethylene solution, removing the solvent from the obtained mixed solution, obtaining an initial composite material, and finally undergoing a molding process to obtain a silicon carbide-polyethylene composite material with laser responsiveness. The present invention utilizes wet nano-dispersion technology, focusing on compounding silicon carbide waste generated by multi-wire cutting with polyethylene to prepare a high-performance laser responsive material, which can not only improve the physical properties of the material, give the material laser responsiveness, but also realize resource utilization. The silicon carbide-polyethylene composite material with laser responsiveness prepared by the present invention not only has excellent mechanical properties, but also can exhibit specific thermal response behavior under laser irradiation, and has broad application prospects.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a silicon carbide-polyethylene composite material having laser responsiveness, the preparation method comprising the following steps:
[0009] (1) pre-treating silicon carbide waste, and uniformly mixing the obtained silicon carbide particles with a first organic solvent and a surfactant to obtain a silicon carbide dispersion;
[0010] (2) mixing the low-density polyethylene particles and the second organic solvent evenly so that the low-density polyethylene particles are completely dissolved to obtain a polyethylene solution;
[0011] (3) adding the silicon carbide dispersion described in step (1) to the polyethylene solution described in step (2), and stirring to obtain a mixed solution;
[0012] (4) removing the solvent from the mixed solution in step (3), and subjecting the obtained initial composite material to a molding process to obtain a silicon carbide-polyethylene composite material having laser responsiveness;
[0013] There is no order of precedence between step (1) and step (2).
[0014] The present invention utilizes wet nano-dispersion technology, focuses on compounding the silicon carbide waste generated by multi-wire cutting with polyethylene, and prepares high-performance laser-responsive materials, which can not only improve the physical properties of the materials, give the materials laser responsiveness, but also realize resource utilization. The laser-responsive silicon carbide-polyethylene composite material prepared by the present invention not only has excellent mechanical properties, but also can exhibit specific thermal response behavior under laser irradiation, and has broad application prospects.
[0015] It should be noted that polyethylene is a crystalline polymer. The product obtained by high-pressure polyethylene production is low-density polyethylene (LDPE), which has a melting point of 110-115°C and a processing temperature of 150-210°C.
[0016] It should be noted that the silicon carbide waste described in step (1) includes silicon carbide waste (such as tiny powders and fragments) generated during the silicon carbide crystal cutting process, which is successively subjected to screening, cleaning and drying and other processing steps to remove impurities and obtain high-purity silicon carbide powder; if necessary, the silicon carbide waste can be further ground or heat-treated to enhance its dispersibility and bonding with the plastic matrix (polyethylene).
[0017] It should be noted that the preparation method of the present invention may also add other additives as needed, such as flow modifiers, toughening agents, etc., to improve the processing properties and toughness of the composite material. Other additives may be added in step (2) to prepare the polyethylene solution.
[0018] As a preferred technical solution of the present invention, in step (1), the first organic solvent includes toluene and / or dichloromethane, and the surface modifier includes a silane coupling agent.
[0019] As a preferred technical solution of the present invention, in step (1), the mass ratio of the silicon carbide particles to the first organic solvent is 1:(4-6), for example, 1:4, 1:4.3, 1:4.5, 1:4.8, 1:5, 1:5.2, 1:5.5, 1:5.8 or 1:6, and the mass ratio of the silicon carbide particles to the surfactant is 1:(0.1-0.3), for example, 1:0.1, 1:0.13, 1:0.15, 1:0.18, 1:0.2, 1:0.23, 1:0.25, 1:0.27 or 1:0.3, etc.
[0020] As a preferred technical solution of the present invention, the average particle size of the silicon carbide particles in the silicon carbide dispersion in step (1) is less than 50 μm.
[0021] As a preferred technical solution of the present invention, the uniform mixing in step (1) includes heating stirring and ultrasonic oscillation performed in sequence, and the heating stirring temperature is 60-80°C, such as 60°C, 65°C, 70°C, 75°C or 80°C.
[0022] It should be noted that the heating and stirring in step (1) of the present invention is carried out at 60-80°C, so that the surface modifier and the silicon carbide surface can react chemically to form small molecular groups with affinity. The purpose of surface modification is to improve the dispersibility of silicon carbide particles and enhance their compatibility with the polyethylene matrix, thereby improving the mechanical properties and thermal stability of the composite material. Furthermore, the mixing in step (1) also includes ultrasonic oscillation. Through ultrasonic oscillation (ultrasonic cleaning machine, power of about 300W, frequency of about 20kHz), the surface-modified silicon carbide particles can be dispersed with high intensity. The dispersion time is controlled within 30 minutes to 1 hour to ensure the uniform distribution of silicon carbide particles. Through the cavitation effect of ultrasound, the particle agglomeration is broken to achieve uniform dispersion of nanoparticles.
[0023] As a preferred technical solution of the present invention, in step (2), the second organic solvent includes toluene and / or dichloromethane, which is used to dissolve polyethylene and serve as a dispersion medium.
[0024] And / or, the mixing in step (2) includes heating and stirring, and the heating and stirring temperature is 80-90°C, for example, 80°C, 81°C, 83°C, 85°C, 86°C, 88°C or 90°C.
[0025] As a preferred technical solution of the present invention, the concentration of the polyethylene solution in step (2) is 5-10wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.
[0026] It should be noted that the concentration of the dissolved polyethylene solution can be controlled as required, usually between 5-10 wt %, to ensure that the particles can be evenly dispersed.
[0027] As a preferred technical solution of the present invention, in step (3), the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:(15-25), for example, 1:15, 1:17, 1:20, 1:21, 1:23 or 1:25, etc.
[0028] It should be noted that the mass ratio of silicon carbide particles in the silicon carbide dispersion and polyethylene in the polyethylene solution determines the ratio of the two in the silicon carbide-polyethylene composite material. If the mass of polyethylene is small, the fluidity of the silicon carbide-polyethylene composite material will become very poor, which is not conducive to the molding process. If the mass of polyethylene is large, there will be fewer silicon carbide particles per unit volume, the average laser response time will be extended, and the tensile strength and wear resistance (wear rate) will decrease.
[0029] And / or, in step (3), the stirring speed is 1500-3000rpm, for example, 1500rpm, 1800rpm, 2000rpm, 2300rpm, 2500rpm, 2700rpm or 3000rpm, and the stirring time is 0.5-1h, for example, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h, etc.
[0030] It should be noted that in step (3) of the present invention, the silicon carbide dispersion is slowly added to the polyethylene solution while stirring to ensure that the two components are evenly mixed. A high shear mixer (such as a high-speed homogenizer) is used to further ensure the uniform distribution of silicon carbide particles in the polyethylene solution through high-speed stirring. The stirring speed is usually controlled to be 1500-3000 rpm, and the stirring time is 0.5-1h.
[0031] As a preferred technical solution of the present invention, the solvent removal in step (4) includes reduced pressure evaporation and / or oven heating to remove excess solvent. At this point, the polyethylene and silicon carbide particles have formed a uniform composite material, and after the solvent is removed, the composite material will present a state similar to plastic particles.
[0032] And / or, the molding process in step (4) includes hot pressing molding or extrusion molding.
[0033] It should be noted that if the molding process adopts extrusion molding, it includes: heating the initial composite material after the solvent is removed to about 160-180°C (the specific temperature depends on the type of polyethylene), and extruding it through a mold to form a desired shape, such as a film, sheet, pipe or profile; if the molding process uses hot pressing molding, it includes: placing the initial composite material after the solvent is removed into a mold, heating and pressurizing (about 170°C, pressure of 10-20MPa), and then cooling and solidifying it into the desired shape.
[0034] In a second aspect, the present invention provides a silicon carbide-polyethylene composite material with laser responsiveness, which is prepared by the preparation method described in the first aspect.
[0035] The laser-responsive silicon carbide-polyethylene composite material prepared by the present invention not only has excellent mechanical properties, but also can exhibit specific thermal response behavior under laser irradiation, and has broad application prospects. Specifically, 1. Laser responsiveness. Efficient photothermal conversion: Silicon carbide particles can efficiently absorb laser energy, especially in the infrared band, and have extremely high efficiency in photothermal conversion; Fast response rate: The surface of the material heats up rapidly under the action of the laser, which can achieve precise heat treatment and local deformation; Uniform thermal diffusion: By optimizing the particle size distribution of silicon carbide, the material has uniform photothermal response characteristics to avoid local overheating. 2. Mechanical properties. High tensile strength: The reinforcing effect of silicon carbide particles significantly improves the tensile strength of the composite material, which is suitable for high-load scenarios; Wear resistance: The high hardness of silicon carbide makes the material exhibit excellent wear resistance and prolongs its service life; Excellent impact resistance: The toughness of polyethylene combined with the hardness of silicon carbide makes the material have strong impact resistance, which is suitable for complex working conditions. 3. Thermal properties. High thermal stability: Silicon carbide particles give the material excellent thermal stability, which can maintain stable performance in high temperature environments; Low thermal expansion coefficient: The material has little dimensional change during heating or cooling, which is suitable for precision devices and high-temperature applications; Excellent thermal fatigue resistance: The performance attenuation is small during multiple thermal cycles, which is suitable for repeated laser processing scenarios. 4. Chemical properties. Antioxidation ability: The introduction of silicon carbide particles significantly enhances the material's antioxidant ability, which can remain stable in corrosive environments; Chemical corrosion resistance: The material can resist the erosion of acids, alkalis and various chemical reagents, and is suitable for special chemical environments. 5. Processing and molding performance. Good moldability: The composite material has high fluidity during the molding process and can be processed into devices of complex shapes. Strong adjustability: By adjusting the filling ratio and particle size of silicon carbide, customized regulation of material properties can be achieved.
[0036] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0037] (1) The present invention utilizes wet nano-dispersion technology, focusing on compounding silicon carbide waste generated by multi-wire cutting with polyethylene to prepare high-performance laser-responsive materials, which can not only improve the physical properties of the materials and give the materials laser responsiveness, but also realize resource utilization.
[0038] (2) The laser-responsive silicon carbide-polyethylene composite material prepared by the present invention has a tensile strength of ≥35 MPa, a thermal stability of ≥125°C, an average laser response time of ≤10 ms, and a wear resistance (wear rate) reduced by 20% compared with pure polyethylene material. It not only has excellent mechanical properties, but also can exhibit specific thermal response behavior under laser irradiation, and has broad application prospects. DETAILED DESCRIPTION
[0039] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a silicon carbide-polyethylene composite material with laser responsiveness, the preparation method comprising the following steps:
[0042] (1) SiC waste (such as tiny powders and fragments) generated during the cutting of SiC crystals is subjected to screening, washing and drying steps to remove impurities. The obtained SiC particles are first ground, mixed with toluene and a surfactant (γ-aminopropyltriethoxysilane), and heated and stirred at 70° C. to obtain a SiC dispersion.
[0043] The mass ratio of the silicon carbide particles, the first organic solvent, and the surfactant is 1:5:0.2; the average particle size of the silicon carbide particles in the silicon carbide dispersion is less than 50 μm.
[0044] (2) mixing low-density polyethylene particles and dichloromethane uniformly, heating and stirring at 80° C. to completely dissolve the low-density polyethylene particles, and obtaining a polyethylene solution with a concentration of 8 wt %;
[0045] (3) according to the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution being 1:20, the silicon carbide dispersion is slowly added to the polyethylene solution, and stirred by a high-speed homogenizer at a stirring speed of 2500 rpm for 0.8 h to obtain a mixed solution;
[0046] (4) removing the solvent from the mixed solution of step (3) by means of reduced pressure evaporation, and the obtained initial composite material is extruded, heated to 170° C., and extruded through a mold to form a desired sheet, thereby obtaining a silicon carbide-polyethylene composite material with laser responsiveness;
[0047] There is no order of precedence between step (1) and step (2).
[0048] Example 2
[0049] This embodiment provides a method for preparing a silicon carbide-polyethylene composite material with laser responsiveness. Compared with Embodiment 1, the only difference is that in step (3), the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:30.
[0050] Example 3
[0051] This embodiment provides a method for preparing a silicon carbide-polyethylene composite material with laser responsiveness. Compared with Embodiment 1, the only difference is that in step (3), the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:25.
[0052] Example 4
[0053] This embodiment provides a method for preparing a silicon carbide-polyethylene composite material with laser responsiveness. Compared with Embodiment 1, the only difference is that in step (3), the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:15.
[0054] Example 5
[0055] This embodiment provides a method for preparing a silicon carbide-polyethylene composite material with laser responsiveness. Compared with Embodiment 1, the only difference is that in step (3), the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:10.
[0056] Comparative Example 1
[0057] This comparative example provides a method for preparing a silicon carbide-polyethylene composite material. Compared with Example 1, the only difference is that: instead of using wet nano-dispersion technology, silicon carbide particles and low-density polyethylene particles are directly mixed uniformly by heating and melting;
[0058] The specific contents are as follows:
[0059] (1) The silicon carbide waste (such as tiny powders and fragments) generated during the silicon carbide crystal cutting process is subjected to screening, cleaning and drying steps in sequence to remove impurities, and the obtained silicon carbide particles are ground;
[0060] (2) The ground silicon carbide particles and low-density polyethylene particles are mixed evenly with a powder mixer, heated to 110° C. for melting to achieve uniform mixing, and extruded and granulated to obtain an initial composite material;
[0061] (3) The obtained initial composite material is heated to 110° C. by extrusion molding, and extruded through a die to form a desired sheet, thereby obtaining a silicon carbide-polyethylene composite material.
[0062] Comparative Example 2
[0063] This comparative example provides a method for preparing a simple polyethylene material, the specific contents of which are as follows:
[0064] Low-density polyethylene particles are prepared, heated to 110° C. by extrusion molding, and extruded through a die to form the desired sheet to obtain a pure polyethylene material.
[0065] The sheet materials obtained in the above examples and comparative examples were subjected to relevant tests on tensile strength, thermal stability (melting temperature), average laser response time, and wear resistance (wear rate), and the specific test results are shown in Table 1.
[0066] Tensile strength: in accordance with GB / T 1040-1992 standard.
[0067] Thermal stability: Take a certain amount of sample in a crucible, and heat it to 600℃ at a rate of 10℃ / min in an air atmosphere of 20mL / min. Obtain the corresponding thermogravimetric analysis (TGA) and thermogravimetric analysis first-order differential (DTG) curves, and the melting temperature can be obtained.
[0068] Average laser response time: Place the sheet material to be tested flat on the operating table, irradiate it with an infrared laser with a wavelength of 1064nm and start timing. Count the time required to generate a laser response. Count the laser response times at 50 different positions and calculate the average value, that is, the average laser response time.
[0069] Wear resistance (wear rate): The friction pair was tested on a HT-1000 ball-disc friction and wear tester with a steel ball of 3 mm in diameter. The test temperature was room temperature, the load was 10 N, the rotation axis speed was 200 r / min, the rotation radius was 4 mm, and the test lasted for 50 min. The average friction coefficient 30 min after the friction process was taken as the friction coefficient of the sample in the friction stable state. The wear amount was obtained by weighing the mass difference of the sample before and after friction using an analytical balance with an accuracy of 10 to 5 g, and the wear rate (A) was calculated using formula (1).
[0070] A=Δm / (ρ·N·2πr·T·V) (1)
[0071] Where: Δm——wear loss, g; ρ——sample density, g / cm 3 ; N——load, N; r——rotation radius; T——test time, min; V——rotation speed, r / min.
[0072] Table 1
[0073]
[0074] Note: “ / ” in the table means there is no corresponding test data.
[0075] From Table 1, we can see the following points:
[0076] (1) The present invention utilizes wet nano-dispersion technology to focus on compounding silicon carbide waste generated by multi-wire cutting with polyethylene to prepare high-performance laser-responsive materials, which can not only improve the physical properties of the materials and give the materials laser responsiveness, but also achieve resource utilization; the silicon carbide-polyethylene composite material with laser responsiveness prepared by the present invention has a tensile strength of ≥35MPa, a thermal stability of ≥125°C, and an average laser response time of ≤10ms. Compared with pure polyethylene materials, the wear resistance (wear rate) is reduced by 20%. It not only has excellent mechanical properties, but also can exhibit specific thermal response behavior under laser irradiation, and has broad application prospects;
[0077] (2) By comparing Examples 1-5, it can be learned that the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution determines the ratio of the two in the silicon carbide-polyethylene composite material, which is a key parameter. Since the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution in Example 2 is 1:30, there is too much polyethylene in the composite material, which reduces the tensile strength and wear resistance (wear rate) of the composite material, and the average laser response time is extended to 12ms; since the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:10, there is too little polyethylene in the composite material, which will cause the fluidity of the silicon carbide-polyethylene composite material to become very poor, which is not conducive to the molding process;
[0078] (3) Comparing Example 1 with Comparative Example 1, since Comparative Example 1 directly mixes silicon carbide particles and low-density polyethylene particles evenly by heating and melting, the silicon carbide particles in the composite material are extremely unevenly distributed, which in turn leads to a large difference in laser response time at different positions, so that the measured average laser response time is as high as 20ms.
[0079] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a silicon carbide-polyethylene composite material with laser responsiveness, characterized in that: The preparation method comprises the following steps: (1) pre-treating silicon carbide waste, and uniformly mixing the obtained silicon carbide particles with a first organic solvent and a surfactant to obtain a silicon carbide dispersion; (2) mixing the low-density polyethylene particles and the second organic solvent evenly so that the low-density polyethylene particles are completely dissolved to obtain a polyethylene solution; (3) adding the silicon carbide dispersion described in step (1) to the polyethylene solution described in step (2), and stirring to obtain a mixed solution; (4) removing the solvent from the mixed solution in step (3), and subjecting the obtained initial composite material to a molding process to obtain a silicon carbide-polyethylene composite material having laser responsiveness; There is no order of precedence between step (1) and step (2).
2. The preparation method according to claim 1, characterized in that: In step (1), the first organic solvent includes toluene and / or dichloromethane, and the surface modifier includes a silane coupling agent.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the silicon carbide particles to the first organic solvent is 1:(4-6), and the mass ratio of the silicon carbide particles to the surfactant is 1:(0.1-0.3).
4. The preparation method according to claim 1, characterized in that: The average particle size of the silicon carbide particles in the silicon carbide dispersion in step (1) is less than 50 μm.
5. The preparation method according to claim 1, characterized in that: The uniform mixing in step (1) includes heating stirring and ultrasonic oscillation performed in sequence, and the temperature of the heating stirring is 60-80°C.
6. The preparation method according to claim 1, characterized in that: Step (2) the second organic solvent comprises toluene and / or dichloromethane; And / or, the uniform mixing in step (2) includes heating and stirring, and the temperature of the heating and stirring is 80-90°C.
7. The preparation method according to claim 1, characterized in that: The concentration of the polyethylene solution in step (2) is 5-10wt%.
8. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of silicon carbide particles in the silicon carbide dispersion to polyethylene in the polyethylene solution is 1:(15-25); And / or, in step (3), the stirring speed is 1500-3000 rpm, and the stirring time is 0.5-1 h.
9. The preparation method according to claim 1, characterized in that: The solvent removal in step (4) comprises evaporation under reduced pressure and / or heating in an oven; And / or, the molding process in step (4) includes hot pressing molding or extrusion molding.
10. A silicon carbide-polyethylene composite material with laser responsiveness, characterized in that: The preparation method is described in any one of claims 1 to 9.